INVESTIGAÇÃO CONFORMACIONAL DA ESTRUTURA COM ATIVIDADE ANTI-HCV DA RIBAVIRINA E VIRAMIDINA E DOS NUCLEOSÍDEOS NATURAIS ADENOSINA E GUANOSINA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
Ribavirin is a similar compound to Guanosine, and it has wide application in antiviral activity against several DNA and RNA viruses. In human cells, the Ribavirin is phosphorylated forming a metabolite which inhibits an enzyme involved in synthesis of guanosine triphosphate. This enzyme is required for viral RNA replication, directly affecting their growth. In the solid state the Ribavirin crystallizes in two different ways. There NMR studies in the literature that deal with the Ribavirin in solution. Recently, tests were performed to treat hepatitis virus with a new drug, Viramidine. Its structure is similar to that of Ribavirin, but there is a change in group carboxyamide, since the carbonyl group is replaced by a C=NH. The Viramidine showed a less harmful and less widespread in the body when compared to Ribavirin. Based on this information, the general objective of the work was the conformational analysis of drug Ribavirin, as theoretical as experimental, and Viramidine just in theoretical calculation. Subsequent calculations were performed to natural nucleosides Adenosine and Guanosine, because they are structurally similar to both drugs. Using the package of programs GAUSSIAN 03 the analysis was performed of a series of scans in two dihedral angles of each structure. Then it was built four potential energy surfaces with HF/6-311G level of theory. The conformations present at the point of minimum energy were optimized in isolated phase. In calculations with solvation routines was performed the execution of single-point, according to the polarizable continuum model (PCM), with level of theory with B3LYP/cc-pVDZ. To explain the conformational preferences of global minimum of each nucleoside or drug analyzed have been used as tools maps of electrostatic potential and natural bonding orbital calculations. It was observed that for drugs there were a variation of stable conformation between the isolated phase and solvation. Only one conformation was the most stable in isolated phase for both drugs and having the same characteristic between them, the hydroxyl's hydrogen connected to carbon 5 of ribose is close to a nitrogen atom of the triazole ring, justifying an intramolecular interaction of the type hydrogen bond that stabilizes these conformations. In medium of polar solvating conformations with greater dipole moment were the most stable since the medium of polar solvating preferred these conformations. For nucleosides were found different results that don´t following the same relations of drugs. It was isolated from the drug capsules, employing simple filtration followed by liquid-liquid extraction with ethyl ether. The organic phase was evaporated with a rotary evaporator thus obtaining the pure Ribavirin. The product was characterized by Infrared Spectroscopy on KBr pellets and Nuclear Magnetic Resonance 1H and 13C NMR in D2O and DMSO-d6. The results obtained were compared with the theoretical results, including theoretical frequencies related to experimental wave numbers and coupling constants for two and three bonds found in the resonance spectra and the results of calculation of the theoretical couling constants.
Keywords: cálculos teóricos; análise conformacional; Ribavirina; theoretical calculations; coformational analysis; Ribavirin; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA